Juridical and Ethical Aspects of the Idea of Peace in Kant - Dörflinger, Bernd (Studia Kantiana, 2016)
The categorical imperative central to Kant's Essay on Perpetual Peace is the imperative: "There ought to be no war!". This imperative is more fundamental than all more specific imperatives that we find in both the preliminary and the definitive articles on perpetual peace, for instance the imperatives that there ought to be no standing armies and that the civil constitution should be republican. In this paper, it will be shown that this general imperative that motivates the Essay on Perpetual Peace can be understood in two ways, namely, first, as an imperative of an ethical law-order and, second, as a juridical imperative of the pure reason of right. Moreover, the considerations on the juridical character of this central imperative will unavoidably lead us to Kant's conception of the law of peoples and to the question whether his differentiated conception of international law is able to cope with the demands of the juridical imperative of peace.